2005
DOI: 10.1002/mus.20340
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin‐induced neurotoxicity and the development of neuropathy

Abstract: The pathophysiology of oxaliplatin-induced neurotoxicity remains unclear, although in vitro studies suggest involvement of voltage-gated Na+ channels. In the present study, clinical assessment was combined with nerve conduction studies (NCS) and nerve excitability studies in 16 patients after completion of oxaliplatin therapy. Chronic neuropathic symptoms persisted in 50% of patients. NCS confirmed abnormalities in symptomatic patients: sensory potentials were significantly low, whereas motor studies remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 195 publications
(184 citation statements)
references
References 54 publications
12
164
2
6
Order By: Relevance
“…The presence of comorbidities in our patient population therefore did not seem to significantly influence the rates of dose reduction and treatment cessation-a finding that supports the hypothesis that comorbidities are not associated with a greater risk of oxaliplatin-induced neuropathy. In fact, earlier trials had not found an association of comorbidities such as diabetes with a greater incidence of oxaliplatin-induced persistent peripheral sensory neuropathy [14][15][16] . On the other hand, our lower proportion of participants with grade 3 neuropathy, treatment cessation, and dose reduction might be explained by the inclusion of participants taking pain medications.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of comorbidities in our patient population therefore did not seem to significantly influence the rates of dose reduction and treatment cessation-a finding that supports the hypothesis that comorbidities are not associated with a greater risk of oxaliplatin-induced neuropathy. In fact, earlier trials had not found an association of comorbidities such as diabetes with a greater incidence of oxaliplatin-induced persistent peripheral sensory neuropathy [14][15][16] . On the other hand, our lower proportion of participants with grade 3 neuropathy, treatment cessation, and dose reduction might be explained by the inclusion of participants taking pain medications.…”
Section: Discussionmentioning
confidence: 95%
“…Objective measures of nerve function reveal further lasting deficits in sensory nerves [11,14,34], suggesting that, rather than recovery, patients undergo adaptation to chronic symptoms [35].…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiological assessment of nerve function was undertaken using conventional nerve conduction studies [14,26] and axonal excitability studies [12,27]. A Medelec Synergy system (Oxford Instruments, Oxfordshire, U.K.) was used for nerve conduction studies of upper and lower limb nerves.…”
Section: Clinical Assessment: Grading Of Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the findings of nerve conduction studies do not always correlate with the severity of sensory neuropathy. For example, it has been shown that the abnormalities of sensory NCV may persist even though the symptoms of oxaliplatininduced neuropathy have been remarkably reduced after discontinuation of oxaliplatin treatment [6].…”
mentioning
confidence: 99%